2020
DOI: 10.1016/j.psj.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium bisulfate amendments on bacterial populations in broiler litter

Abstract: The accumulation of ammonia in poultry houses is of concern to bird and human health. Acidification of the litter by application of acidifying amendments such as sodium bisulfate ( SBS ) retains ammonia generated by microbial degradation of uric acid as harmless ammonium in the litter. Although some studies on the effects of litter amendments on specific bacteria and groups of bacteria have been carried out previously, wide gaps in knowledge remain. In the present study, 2 types of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Joerger et al. (2020) also reported an increase in E. coli populations after NaHSO 4 was added to reused litter microcosms. Further studies on the characteristics of such E. coli strains are necessary to investigate whether topdressing and/or applying acidifiers to reused litter has a negative impact on litter health.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Joerger et al. (2020) also reported an increase in E. coli populations after NaHSO 4 was added to reused litter microcosms. Further studies on the characteristics of such E. coli strains are necessary to investigate whether topdressing and/or applying acidifiers to reused litter has a negative impact on litter health.…”
Section: Discussionmentioning
confidence: 93%
“…but also have resulted in a bloom in fungi population (Cook et al, 2008(Cook et al, , 2011Hunolt et al, 2015;Kassem et al, 2012;Line & Bailey, 2006;Rothrock et al, 2008;Williams et al, 2012). Recently, Joerger et al (2020) demonstrated that the application of sodium bisulfate (NaHSO 4 ) to fresh pine shavings amended with chicken feces microcosms resulted in an increase in Escherichia 16S rRNA gene sequences and suggested that higher ammonia levels caused suppression of Escherichia spp., whereas lower pH and lower free ammonia levels allowed persistence of members of this genus (Joerger et al, 2020).…”
mentioning
confidence: 99%
“…The pH of reused litter was higher (7.12 ± 0.26) than fresh litter (6.54 ± 0.17) ( P = 0.028), while fresh litter had higher moisture (20.83 ± 3.54 %) than reused litter (14.65± 3.51 %) ( P = 0.11). Litter moisture and pH are known factors that affect pathogen survival and microbial diversity [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…However, ventilation may be limited to conserve energy, especially during colder months [ 21 ]. Growers commonly use acidifying litter amendments to induce short-term reductions of ammonia emissions, but they usually do not affect moisture content in the litter and their efficacy at reducing microbial loads is inconclusive [ [22] , [23] , [24] , [25] ]. Absorbent litter amendments that improve the water holding capacity of broiler litter may influence microbial communities by limiting water availability; however, their effectiveness has not been examined in the context of live broiler production.…”
Section: Introductionmentioning
confidence: 99%